2018
DOI: 10.1002/da.22768
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric morbidity in United States military spouses: The Millennium Cohort Family Study

Abstract: One third of junior military spouses screened positive for one or more psychiatric conditions, underscoring the need for high-quality prevention and treatment services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 52 publications
1
27
0
Order By: Relevance
“…The purpose of this study was to investigate whether supplementation with omega-3 HUFAs from a krill oil concentrate (PL), with its possible advantages in bioavailability and high amount of PC, will improve emotional status and related cognitive performance under stress among IBOLC students (Phase I) and subsequent RC (Phase II). More broadly, approximately 35% of military spouses report stress related psychiatric illnesses [ 54 ]. A potential impact of this study would be information that would support the role for krill oil concentrate containing omega-3 HUFAs in contributing to improving mood, emotional status and cognitive performance among the US population in general [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to investigate whether supplementation with omega-3 HUFAs from a krill oil concentrate (PL), with its possible advantages in bioavailability and high amount of PC, will improve emotional status and related cognitive performance under stress among IBOLC students (Phase I) and subsequent RC (Phase II). More broadly, approximately 35% of military spouses report stress related psychiatric illnesses [ 54 ]. A potential impact of this study would be information that would support the role for krill oil concentrate containing omega-3 HUFAs in contributing to improving mood, emotional status and cognitive performance among the US population in general [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the early stages of the wars in Iraq and Afghanistan, the prevalence of mental health concerns among the spouses of active duty service members who deployed mirrored those of service members (Eaton et al, 2008). More recently, Steenkamp et al (2018) found that over one‐third of the spouses of a large probability‐sampled cohort study of U.S. junior military personnel met criteria for at least one mental disorder. Mental disorders in their sample were especially prevalent among the spouses of combat deployed, as compared with noncombat deployed and nondeployed, service members.…”
Section: Introductionmentioning
confidence: 99%
“…Third, research in this area has typically relied on assessment of psychopathology solely with written questionnaires, which are often more vulnerable to reporting biases than structured interviews (McDonald & Calhoun, 2010). Finally, the literature has relied primarily on small convenience or clinical samples, although exceptions exist (e.g., Steenkamp et al, 2018; Tanielian, Karney, Chandra, & Meadows, 2014). Steenkamp et al (2018), for example, examined diagnostic concordance, including depression, within dyads in a large, population‐based sample of service members and spouses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For one, the stress experienced by active duty spouses can sometimes be severe, as when their spouse participates in active conflict or when spouses are otherwise separated for long periods of time as part of a deployment (Eaton et al, 2008;Steenkamp et al, 2018). The military has long been acknowledged as a "greedy" institution, demanding extraordinary commitment, sacrifice, and patience for those who serve in it (Segal, 1986).…”
Section: Introductionmentioning
confidence: 99%